Post-filter ionized calcium target adjusted during simplified regional citrate anticoagulation during postdilution continuous veno-venous hemodiafiltration therapy - Liu Zhao; Zeng Yi-qian; Yuan Jiao; Zeng Wei-zhong; Peng Su-na (Linchuang shenzangbing zazhi)
ObjectiveTo explore whether or not bubble chamber ionized calcium（iCa） attained the range of target concentrations during simplified regional citrate anticoagulation during postdilution continuous veno-venous hemodiafiltration （CVVHDF）. If not，further research was performed for seeking novel postfilter ionized calcium goal-setting.MethodsA total of 62 patients with simplified regional citrate anticoagulation in postdilution CVVHDF therapies in intensive care unit （ICU） were recruited and randomized into two groups of treatment （n=30，16 males and 14 females） and control （n=32，16 males and 16 females）. Postfilter iCa was employed a parameter for monitoring the target of control group while return line iCa for monitoring the target of treatment group. The samples were collected for circuit postfilter and venous iCa as well as peripheral blood iCa. Meanwhile，other related data such as bubble chamber clotting and circuit lifespan were recorded.ResultsPostfilter ionized calcium levels in both groups were significantly higher than return line. Circuit lifespan increased in treatment group as compared with control group. Postfilter ionized calcium level ［（0.28±0.05）mmol/L］ was significantly lower in treatment group than control group when bubble chamber ionized calcium attained the range of target concentrations.ConclusionIt may provide a longer circuit lifespan and reduce chamber clotting during simplified regional citrate anticoagulation in postdilution CVVHDF therapies when postfilter ionized calcium level is not higher than 0.28 mmol/L.